The Influence of Social Support and Relationship Quality on Behavioral Intention in Social Commerce - Erwin Sugiharto (Journal of Multidisciplinary Issues, 2023)
Purposes - This study aims to examine the impact of social support and website quality on user engagement and behavioral intention within the realm of social commerce. It seeks to understand how these factors influence users' motivation to participate in social commerce activities and make purchasing decisions on social media platforms. Methodology - A quantitative research approach was employed, gathering data from 68 respondents through an online survey. The collected data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The analysis included the assessment of the measurement model (outer model) and the structural model (inner model), followed by hypothesis testing through bootstrapping. Findings - The study found that social support and website quality have significant positive effects on user engagement and behavioral intention in social commerce. After adjusting for invalid indicators, the revised PLS-SEM analysis confirmed that all variables were reliable and valid, with Average Variance Extracted (AVE) values of ≥ 0.5 and Cronbach's alpha of ≥ 0.7. Social influence emerged as a key driver of behavioral intention. Novelty - This research contributes to the existing literature by providing empirical evidence on the direct impact of social support and website quality on behavioral intention in social commerce. It also demonstrates the application of PLS-SEM in examining the intricate relationships between these variables, offering a methodological approach for future studies in this domain. Research Implications - The findings suggest that businesses should prioritize enhancing social support and website quality to improve customer engagement and satisfaction in social commerce. Additionally, businesses must carefully manage their social media presence to maintain positive social influence, as this directly affects users' purchasing behavior. Future research should explore the effects of technological advancements and external factors such as regulatory policies on social commerce dynamics.